1986
DOI: 10.1044/jshr.2901.37
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral Air Pressure and Oral Air Flow Under Different Bleed and Bite-Block Conditions

Abstract: Intraoral pressures and oral flows were measured as normal talkers produced /p/ and /si/ under experimental conditions that perturbed the usual aeromechanical production characteristics of the consonants. A translabial pressure-release device was used to bleed off intraoral pressure during /p/. Bite—blocks were used to open the anterior bite artificially during /s/. For /p/, intraoral pressure decreased and translabial air leakage increased as bleed orifice area increased. For /s/, flow increased as the area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…The effect of speaking rate on intraoral pressure is important to examine as this measure has been viewed as a controlled parameter in speech (Kim, Zajac, Warren, Mayo, & Essick, 1997;Klechak, Bradley, & Warren, 1976;Putnam, Shelton, & Kastner, 1986;Warren, Hall, & Davis, 1981;Warren, 1982;Warren, 1986;Warren, Morr, Rochet, & Dalston, 1989). Based on the increased oral airflows observed at greater VP port openings in normal speakers and in those with open bite, Warren hypothesized that respiratory adjustments serve to maintain adequate levels of intraoral pressure during speech (Klechak et al, 1976;Warren et al, 1981;Warren, 1982).…”
Section: Aerodynamic Measures Of Vp Function and Rate Variationsmentioning
confidence: 99%
“…The effect of speaking rate on intraoral pressure is important to examine as this measure has been viewed as a controlled parameter in speech (Kim, Zajac, Warren, Mayo, & Essick, 1997;Klechak, Bradley, & Warren, 1976;Putnam, Shelton, & Kastner, 1986;Warren, Hall, & Davis, 1981;Warren, 1982;Warren, 1986;Warren, Morr, Rochet, & Dalston, 1989). Based on the increased oral airflows observed at greater VP port openings in normal speakers and in those with open bite, Warren hypothesized that respiratory adjustments serve to maintain adequate levels of intraoral pressure during speech (Klechak et al, 1976;Warren et al, 1981;Warren, 1982).…”
Section: Aerodynamic Measures Of Vp Function and Rate Variationsmentioning
confidence: 99%
“…Also palatal surgery may cause maxillary growth deficits which constrict the nasal floor, reduce airway size, and increase airway resistance [11]. Since articulation is the last motor stage of speech after respiration, phonation, and resonance, many studies have focused on the control and regulation of breathing and aerodynamic variables during speech sound production [12][13][14][15]. Our preliminary findings showed that low laryngeal resistance (LARE) was significantly associated with /r/ distortions, whereas nasal cross-sectional area (NASA), nasal resistance (NASAR) and velopharyngeal orifice area (VEPA) were not related to the /r/-sound distortions in cleft patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…Warren [7] has noted that the term 'control' generally implies that the brain receives information, processes it, and then directs the control activity. Evidence for this has been accounted for in air leak [20,25,26] and bite block [27] studies, thus prompting Warren et al [24] to postulate that 'the respiratory and articulatory structures are constrained to act together toward a common goal of maintaining an adequate level of pressure for consonants'. The results of the present study have revealed that speakers possess the ability to detect differences in self-generated oral air pressures that are at or below the values known for differences between consonant cognate pairs.…”
Section: Discussionmentioning
confidence: 99%